Reflexões sobre as teorias de potência elétrica em regime não senoidal - Lima, Ezequiel Junio de (2014)
The development of an electric power theory under nonsinusoidal conditions is a wide and complex topic. The first researches in the area date back from 1927 and 1932 and, up to now, there is no consensus. The main issue is to understand how the power flows in an electric circuit works since classic definitions of electric power, presented in engineering textbooks, do not reliably depict the energy flow\'s interactions in systems with distorted voltage and current waveforms. In this context, the qualification and quantification of reactive power is the most controversial. Thus, this dissertation aims to contribute to studies in non-sinusoidal systems with focus on power definitions with a special attention to reactive power and its implications. Some comments on the active power are also made.